2015
DOI: 10.1113/jphysiol.2014.282889
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted hippocampal sharp‐wave ripple‐associated spike dynamics in a transgenic mouse model of dementia

Abstract: Key pointsr High frequency (100-250 Hz) neuronal oscillations in the hippocampus, known as sharp-wave ripples (SWRs), synchronise the firing behaviour of groups of neurons and play a key role in memory consolidation.r Learning and memory are severely compromised in dementias such as Alzheimer's disease; however, the effects of dementia-related pathology on SWRs are unknown.r The frequency and temporal structure of SWRs was disrupted in a transgenic mouse model of tauopathy (one of the major hallmarks of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 61 publications
14
74
0
Order By: Relevance
“…Tau within the MTL diminishes the expression of hippocampal ripples in rodents, resulting in less temporally synchronized ripple events 104 . This desynchrony is, in part, due to loss of GABA-dependent inhibition that dictates patterned neural firing and thus governs neural oscillations 104 .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Tau within the MTL diminishes the expression of hippocampal ripples in rodents, resulting in less temporally synchronized ripple events 104 . This desynchrony is, in part, due to loss of GABA-dependent inhibition that dictates patterned neural firing and thus governs neural oscillations 104 .…”
Section: Figurementioning
confidence: 99%
“…This desynchrony is, in part, due to loss of GABA-dependent inhibition that dictates patterned neural firing and thus governs neural oscillations 104 . Tau is further associated with abnormally long hyperpolarized down states and impaired depolarizing up states during NREM slow oscillations within the cortex 105 .…”
Section: Figurementioning
confidence: 99%
“…In vivo electrophysiological recordings. Methods were as described previously (Witton et al, 2014). Briefly, mice were implanted with custom microdrives containing four independently movable tetrodes.…”
Section: Methodsmentioning
confidence: 99%
“…Work in this model has revealed tauopathy-associated morphological and electrophysiological changes in rTg4510 cortical neurons, including dendritic and synaptic atrophy, depolarization of the resting potential, and increased "sag" potentials (Rocher et al, 2010;Crimins et al, 2011Crimins et al, , 2012. Furthermore, recent work has identified disturbances to hippocampal sharp wave-ripple oscillations (Witton et al, 2014) and spatial encoding in rTg4510 mice (Cheng and Ji, 2013), suggesting a level of hippocampal network dysfunction. Thus, it is apparent that tau-associated neuropathology induces changes in neuronal cellular and network physiology, likely leading to cognitive behavioral impairments in tasks dependent on these circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from optogenetically driven gamma oscillations in mEC slices suggests that the disruption in theta-gamma cross-frequency coupling might arise from impairment in excitatory drive onto fast-spiking interneurons (Pastoll et al, 2013). Indeed, we have recently reported that glutamatergic drive on to CA1 hippocampal interneurons is defective in rTg4510 mice (Witton et al, 2014), contributing to an emerging picture of the disruption of GABAergic circuits in mouse models of dementia (Driver et al, 2007;Palop et al, 2007;Baglietto-Vargas et al, 2010;Verret et al, 2012).…”
Section: Alterations In Rtg4510 Mice Compared With Wt Micementioning
confidence: 99%